2012
DOI: 10.1007/s00221-012-3336-9
|View full text |Cite
|
Sign up to set email alerts
|

Motor transfer from map ocular exploration to locomotion during spatial navigation from memory

Abstract: Spatial navigation from memory can rely on two different strategies: a mental simulation of a kinesthetic spatial navigation (egocentric route strategy) or visual-spatial memory using a mental map (allocentric survey strategy). We hypothesized that a previously performed "oculomotor navigation" on a map could be used by the brain to perform a locomotor memory task. Participants were instructed to (1) learn a path on a map through a sequence of vertical and horizontal eyes movements and (2) walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…A novel test for locomotor navigation, suitable for both children and adults, has been developed for the study of spatial orientation, visual–spatial memory, and cognitive strategies during navigation: the Magic Carpet (MC) ( Meilinger et al, 2011 ; Demichelis et al, 2013 ; Belmonti et al, 2014 ; Perrochon et al, 2014 ). The MC was derived from the previous Walking–Corsi test ( Piccardi et al, 2008 ), and both are transpositions of the traditional Corsi Block-tapping Task (CBT) to locomotor space.…”
Section: Introductionmentioning
confidence: 99%
“…A novel test for locomotor navigation, suitable for both children and adults, has been developed for the study of spatial orientation, visual–spatial memory, and cognitive strategies during navigation: the Magic Carpet (MC) ( Meilinger et al, 2011 ; Demichelis et al, 2013 ; Belmonti et al, 2014 ; Perrochon et al, 2014 ). The MC was derived from the previous Walking–Corsi test ( Piccardi et al, 2008 ), and both are transpositions of the traditional Corsi Block-tapping Task (CBT) to locomotor space.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effect was amplified when the participants were right-handed. Demichelis et al (2013) investigated whether, when attempting to restore walking a path learned on a map from our memory, we remember it by simulating the ocular exploration that we originally used to learn it. In one hand the results showed that horizontal movements being more efficient than vertical ones, in other hand, they suggest that the participants had mentally repeated their previous ocular exploration of the map, and that it is this oculomotor memory that was used to perform the locomotor memory task.…”
mentioning
confidence: 99%
“…We have shown that gaze (as evidenced by eye and head direction in space) anticipates the trajectory and that the control of walking is a top‐down mechanism in which gaze control is essential. The importance of gaze in the planning of walking trajectories has also been shown in the ‘magic carpet’ paradigm (see below) . To study the anticipation of the locomotor trajectory by gaze and the problem of spatial reference frames in these children, we have designed a paradigm (Fig.…”
Section: The ‘Locomotor Trajectory’ Paradigmmentioning
confidence: 99%
“…The importance of gaze in the planning of walking trajectories has also been shown in the 'magic carpet' paradigm (see below). 5 To study the anticipation of the locomotor trajectory by gaze and the problem of spatial reference frames in these children, we have designed a paradigm ( Fig. 2) in which the child has to reach, by walking in a room, one of three visual targets from an initial departure point.…”
Section: The 'Locomotor Trajectory' Paradigmmentioning
confidence: 99%